2023
DOI: 10.3389/fpubh.2023.1068268
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Canadian perceptions and experiences of stigma during the COVID-19 pandemic

Abstract: BackgroundThe COVID-19 pandemic has led to stigmatization of individuals based on race/ethnicity, age, gender, and occupation, among other factors. We canvassed Canadian residents to explore perceptions of and experiences with stigma during the COVID-19 pandemic.MethodsWe conducted an online survey between June 10 and December 31 2020. The survey was rooted in the Health Stigma and Discrimination Framework and included multiple choice, Likert and open-ended questions related to perceived and experienced stigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…First, East-Asian participants called on the Canadian government to champion messaging to reduce stigmatizing and racist rhetoric. Our study did not directly explore the link between exposure to misinformation and perceptions or experiences of stigmatization, yet we posit that the rise of stigmatizing information directly impacted the experiences of East Asian individuals living in Canada during the pandemic [29]. COVID-19 related information was often laden with stigmatizing messages, which were shared widely on mainstream and social media channels.…”
Section: Discussionmentioning
confidence: 95%
“…First, East-Asian participants called on the Canadian government to champion messaging to reduce stigmatizing and racist rhetoric. Our study did not directly explore the link between exposure to misinformation and perceptions or experiences of stigmatization, yet we posit that the rise of stigmatizing information directly impacted the experiences of East Asian individuals living in Canada during the pandemic [29]. COVID-19 related information was often laden with stigmatizing messages, which were shared widely on mainstream and social media channels.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple studies have demonstrated the link between inconsistent, unclear vaccination policies and a rise of vaccine hesitancy (Vernon-Wilson et al, 2023). These policies reinforced doubts about the vaccines and fueled mistrust of health organizations, especially among historically marginalized communities (Fahim et al, 2023b;Fahim et al, 2023a;Theivendrampillai et al, 2023). These sentiments extended to LTCH/RH and other healthcare staff, with high levels of vaccine hesitancy reported as the vaccines were first rolled out (Murmann et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Our survey was composed of 2 sections. The first section explored perceptions of stigma during the COVID-19 pandemic; these results are reported elsewhere [ 8 ]. The second section explored preferred sources of acquiring COVID-19 information during the first and second waves of the COVID-19 pandemic in Canada, perceptions of encountering misinformation during the pandemic, trust in information sources, and suggestions on how to optimize public health messaging.…”
Section: Methodsmentioning
confidence: 99%